PENGARUH BEAUTY VLOGGER TERHADAP KEPUTUSAN PEMBELIAN PRODUK KECANTIKAN OLEH KONSUMEN GEN Y DAN GEN Z - Dinda Tiara Luqman; Aida Sari; Dwi Asri Sit; Driya Wiryawan (Jurnal Ekonomi Bisnis dan Akuntansi, 2022)
The effect of Beauty Vlogger's video on the buyer's interest in buying a beauty product is significant. It means that in this case it's certainly becoming new as one of the innovations in advertising. That is why the Author is interested in discussing the material regarding these conditions. The purpose of writing articles on this issue is to compare and test the validity of Beauty Vlogger's influence as a form of innovation itself as the digital world continues to grow, especially in advertising or endorsement. The author uses quantitative methods in writing this article. Where in this case the author not only presents actual facts, but also in his writing provides accurate data. Research has shown that Beauty Vlogger's significance, personality, appearance, and popularity greatly influenced the public in making decisions about which beauty products to choose.